LINGUISTIC LANDSCAPE - Čalovková, Simona (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
This article focuses on a new branch of sociolinguistics, called linguistic landscape studies, which is understood as an attempt to investigate the publicly visible languages on billboards, road and safety signs, shop signs, graffiti and all sorts of other inscriptions in the public space. According to linguistic landscape studies, language is seen as the most immediate and direct identifier of people and the most immediately sensitive indicator of social change. Generally speaking, linguistic landscape is around us all the time, but we usually do not notice it, as we are probably not aware of the languages on the streets. A growing interest in this topic is the main theme of this article, which can be understood as an overview of the approaches to the linguistic landscape field presented by the various scholars.